Implementasi Media Mindmapping pada Pelajaran SKI Berbasis Kurikulum Merdeka di MA Mambaul Ulum Megaluh Jombang - Aizzah, Shilna; Waslah, Waslah; Huda, Saihul Atho Alaul (Lembaga Yasin AlSys, 2025)
This research was motivated by a sense of boredom and saturation in SKI learning due to the many historical stories that cover a wide range and the names of figures that are difficult to memorize. The purpose of this study was to determine the response of students when implementing mind mapping learning media in SKI subjects based on the independent curriculum. The method used in this study is a qualitative method. This research was conducted at MA Mambaul Ulum Megaluh Jombang. The subjects in this study were the principal, curriculum vice principal, SKI subject teachers, and class X students. Data collection techniques in this study were observation, interviews, and documentation. The results of the implementation of mind mapping learning media in SKI subjects based on the independent curriculum received a good response from the school, the response of students regarding mind mapping learning media in SKI subjects based on the independent curriculum was that students found it easier to understand, the summary of the material taught became short and clear, and created a fun and enjoyable learning atmosphere. The advantages of this mind mapping learning media are to train students to be more creative, easier to understand, and the material taught becomes short and clear. Meanwhile, the drawbacks of this mind mapping learning media are that its creation requires a long process and time. This shows that mind mapping media can be applied in the SKI learning process to increase the creativity and activeness of students.